2020
DOI: 10.1080/16583655.2020.1782601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aminopyridinium-based ionic liquids against larvae ofCulex pipiens(Diptera: Culicidae)

Abstract: Culex pipiens is the most abundant mosquito in Al-Madinah Al-Munawwarah region, Saudi Arabia, transmitting several diseases like elephantiasis, avian malaria, and arboviruses. It has become resistant to several insecticides worldwide, and the search for new alternatives should be prioritized. Because of their biological profile and eco-friendly nature, ionic liquids (ILs) have recently attracted the attention of biologists. The present study was carried out to evaluate the effect of six ILs against C. pipiens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 55 publications
1
10
0
1
Order By: Relevance
“…new safe and degradable compounds should be encouraged for controlling mosquitoes. This study highlights the promising potential of ILs as practical alternatives to conventional insecticides [56]. Similar recent studies showed that numerous plant extracts and Eucalyptus oil have a potent effect at lower concentrations against larvae and pupae of different mosquito species [75,76].…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…new safe and degradable compounds should be encouraged for controlling mosquitoes. This study highlights the promising potential of ILs as practical alternatives to conventional insecticides [56]. Similar recent studies showed that numerous plant extracts and Eucalyptus oil have a potent effect at lower concentrations against larvae and pupae of different mosquito species [75,76].…”
Section: Discussionsupporting
confidence: 71%
“…Pupae alongside larvae of C. pipiens were collected from the DWW drain area of Saad Al-Ghab [56]. Numerous water samples were collected and poured into 5L containers, The sampled water with larvae and pupae was then transferred into plastic trays (25 × 25 × 15 cm) which were 2/3 filled and kept at 24 ± 2°C for further experiments.…”
Section: Ovicidal and Pupicidal Bioassaymentioning
confidence: 99%
See 3 more Smart Citations